2007
DOI: 10.1007/s11248-007-9120-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of novel ketocarotenoid production in carrot plants

Abstract: Carotenoids constitute a vast group of pigments that are ubiquitous throughout nature. Carrot (Daucus carota L.) roots provide an important source of dietary beta-carotene (provitamin A), alpha-carotene and lutein. Ketocarotenoids, such as canthaxanthin and astaxanthin, are produced by some algae and cyanobacteria but are rare in plants. Ketocarotenoids are strong antioxidants that are chemically synthesized and used as dietary supplements and pigments in the aquaculture and neutraceutical industries. We engin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(66 citation statements)
references
References 47 publications
0
66
0
Order By: Relevance
“…A similar effort was made with a carrot plant, resulting in a comparable amount (ca. 916 μg g -1 dwt) of astaxanthin in root tissues (Jayaraj et al 2008). Expression of a Chlamydomonas BKT into Arabidopsis led to the accumulation of greater amounts of astaxanthin (up to 2,000 μg g -1 dwt) in leaves of the transgenic plant, whereas the expression of C. zofingiensis BKT only resulted in 240 μg astaxanthin g -1 dwt .…”
Section: Metabolic Engineering For Enhanced Carotenoid Productionmentioning
confidence: 93%
“…A similar effort was made with a carrot plant, resulting in a comparable amount (ca. 916 μg g -1 dwt) of astaxanthin in root tissues (Jayaraj et al 2008). Expression of a Chlamydomonas BKT into Arabidopsis led to the accumulation of greater amounts of astaxanthin (up to 2,000 μg g -1 dwt) in leaves of the transgenic plant, whereas the expression of C. zofingiensis BKT only resulted in 240 μg astaxanthin g -1 dwt .…”
Section: Metabolic Engineering For Enhanced Carotenoid Productionmentioning
confidence: 93%
“…Underground food crops, such as potato and carrot have also been engineered to have increased carotenoid content, in particular b-carotene and ketocarotenoids (e.g. astaxanthin), which produce a deep yellow ('golden') potato tuber phenotype and a distinct pink to deep red colour compared with the typical orange colour in wild-type carrot roots (Taylor and Ramsay 2005;Diretto et al 2007;Jayaraj et al 2008). Finally, the overexpression of PSY in Arabidopsis increased carotenoid content by 10-to 100-fold in nonphotosynthetic calli and roots, predominantly b-carotene and its derivatives, which were deposited as crystals in storage plastids (Maass et al 2009).…”
Section: Accumulation Storage and Insights From Bioforticationmentioning
confidence: 99%
“…This finding coincides with our results of the complementation experiments using E. coli transformants. As for practical plants, several ketolase genes were tried to be expressed in several crops, i.e., tomato, potato and carrot plants (Rally et al 2004;Morris et al 2006;Gerjets and Sandmann 2006;Jayaraj et al 2008). The bkt1 and crtO genes were individually introduced into potato plants, and resultant transgenic plants were found to produce ketocarotenoids including astaxanthin in the tuber tissues (Morris et al 2006;Gerjets and Sandmann 2006), as shown in Table 1.…”
Section: Expression Of a B B-carotene Ketolase Gene In Plantsmentioning
confidence: 99%
“…The bkt1 and crtO genes were individually introduced into potato plants, and resultant transgenic plants were found to produce ketocarotenoids including astaxanthin in the tuber tissues (Morris et al 2006;Gerjets and Sandmann 2006), as shown in Table 1. Jayaraj et al (2008) expressed the bkt1 gene in carrot roots using the double CaMV 35S promoter, and found that the transgenic roots were able to accumulate large amounts of ketocarotenoids (236 mg g Ϫ1 fresh weight; 68% of total carotenoids) containing 91.6 mg g Ϫ1 fresh weight of astaxanthin, 57.0 mg g Ϫ1 fresh weight of adonirubin and 50.1 mg g Ϫ1 fresh weight of canthaxanthin (Table 1). Recently, Hasunuma et al (2008) introduced the genes [crtW (SD212) and crtZ (SD212)] encoding the CrtW and CrtZ proteins of Asterisks indicate data for dry weight of tissue.…”
Section: Expression Of a B B-carotene Ketolase Gene In Plantsmentioning
confidence: 99%
See 1 more Smart Citation